2020
DOI: 10.3390/ijerph17020463
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Myopia in Adolescents through Machine Learning Methods

Abstract: According to literature, myopia has become the second most common eye disease in China, and the incidence of myopia is increasing year by year, and showing a trend of younger age. Previous researches have shown that the occurrence of myopia is mainly determined by poor eye habits, including reading and writing posture, eye length, and so on, and parents’ heredity. In order to better prevent myopia in adolescents, this paper studies the influence of related factors on myopia incidence in adolescents based on ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Existing studies have suggested that the prevalence of myopia in grade 3 children increased from 13.3% at the end of 2019 to 20.8% at the end of 2020 [4]. In addition, wrong eye posture and prolonged irregular eye use are also some of the important factors leading to vision loss [5][6][7]. Most studies in China and abroad regarding the impact of reading and writing postures on myopia have focused on examining the viewing distance, chest-table distance, viewing angle, and viewing duration.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have suggested that the prevalence of myopia in grade 3 children increased from 13.3% at the end of 2019 to 20.8% at the end of 2020 [4]. In addition, wrong eye posture and prolonged irregular eye use are also some of the important factors leading to vision loss [5][6][7]. Most studies in China and abroad regarding the impact of reading and writing postures on myopia have focused on examining the viewing distance, chest-table distance, viewing angle, and viewing duration.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al ( 45 ) identified myopia development rules and predicted the onset of myopia and its progression for children and teenagers from clinical measures using a random forest ML model, which had good predictive performance (the AUC ranged from 0.801 to 0.837) for up to 8 years in the future. Yang et al ( 46 ) developed a prediction model to predict myopia in adolescents based on both measurement and behavior data of primary school students, and the model achieved reasonable performance and accuracy. Further research is still required for interpopulation validation to allow these models to be generalized.…”
Section: Ai In the Prediction Of Myopia Progressionmentioning
confidence: 99%
“…[23][24][25] As myopia continues to be a leading and growing cause of visual impairment globally, it remains to be seen how this proof of efficacy might translate into effective and scalable systems of care and how AI might play a role in the care pathway. 26 One particularly intriguing case of rapidly scaling technology is the smartphone-based mobile refractometer available via GoCheck Kids. 27,28 This cloud-base service provides point-of-care diagnosis of refractive error for use in the primary care setting and has created a datarich environment that has now used AI to improve end-user actions to capture the best image possible to improve the diagnostic accuracy.…”
Section: Refractive Errormentioning
confidence: 99%